Validation of Methods and Determination of Curcumin Levels in Carrying Herbal Medicine of Turmeric Tamarind Using UV-Vis Spectrophotometer - Arum Dwi Nanda, Arum; Khusna Santika Rahmasari, Khusna; Achmad Vandian Nur, Vandian; apt. Eko Mugiyanto, Eko (Indonesian Journal of Chemical Science, 2025)
Turmeric contains curcumin which works to increase the body's defense system against viruses or bacteria. The study aims to determine the validity parameters in the form of linearity, precision, accuracy, LOD, LOQ and determine the curcumin levels in carrying herbal medicine of turmeric tamarind. Method validation aims to ensure that the method to be used meets the requirements for the analytical application and can be justified for its correctness. The method was quantitative one using UV-Vis spectrophotometer. The results showed that the method met the linearity requirements with r: 0.9995, accuracy with a recovery value of 99.43%, precision with an RSD value of 0.49%, and LOD and LOQ with values of 0.0054 µg/mL and 0.0163 µg/mL. The curcumin content in the herbal medicine of turmeric tamarind sold at Ulujami Market, Pemalang in herbal medicine sample A was 0.09% and herbal medicine sample B was 0.07%.